Improving Critical Thinking Skills and Learning Outcomes of 4th Grade Students Through Discovery Learning Model - Wahyu Rizaldi; Mawardi Mawardi (JETL (Journal of Education, Teaching and Learning), 2021)
Lack of critical thinking skills in students is a problem faced in thematic learning at SD Negeri 2 Kedungrejo. Therefore, it had an impact on low learning outcomes. From this problem, this study aims to improve critical thinking skills and learning outcomes through discovery learning model. Classroom Action Research (PTK) was used in this study. While the data collection instruments included observation sheets, test questions, and questionnaires. The data analysis technique used a comparative descriptive technique. The subjects of this study were 22 4th grade students of SD Negeri 2 Kedungrejo. The results of this study indicated an improvement of critical thinking skills and students’ learning outcomes. This can be proven by the average value of students' critical thinking skills in cycle I of 54.67% and increased again in cycle II by 69.84%. Whereas for students’ learning outcomes, in cycle I showed students’ average score of 70. Moreover, it increased by an average value of 80 in cycle II. To sum up, these results showed that applying discovery learning model in the online learning process were able to improve students’ critical thinking skills and learning outcomes.